Bottlenecks to financial development, financial inclusion, and microfinance: A case study of Mauritania - Mohamedou Bouasria; Arvind Ashta; Zaka Ratsimalahelo (Journal of Risk and Financial Management, 2020)
The objective of the study was to enhance our knowledge on institutional bottlenecks for financial development, financial inclusion, and microfinance, using Mauritania as a case study. We used a mixed-methods' methodology that combines analysis of secondary data and an expert interview. First, a logit model with dummy independent variables was used to investigate the factors that impact the households' access to credit, the main advantage of this model being to avoid confounding effects by analyzing the association of all variables together. Our study found that access to financial services is equal in Mauritania between men and women, but that access to credit is higher for public sector employees, educated people, and households with smaller families. Second, using principal components' analysis, we found that the different regions of Mauritania can be divided based on unemployment, income, literacy, financial inclusion, and population density into two main dimensions, yielding four quadrants: Attractive, industrious, moderate, and resource cursed. We expected that sparsely populated countries would have less access to credit. Counterintuitively, we found that within a low-density country, people in the lowest-density regions have higher odds of getting credit. Third, based on an interview with an expert, we noted the key challenges that microfinance is facing in Mauritania and provided recommendations to overcome these. As in most case studies, external validity was limited.
Keywords: 330; financial inclusion; population density; logit model; microcredit; microfinance; regional analysis